2019
DOI: 10.3928/24748307-20190306-03
|View full text |Cite
|
Sign up to set email alerts
|

A Readability Analysis of Online Cardiovascular Disease-Related Health Education Materials

Abstract: Background: Online cardiovascular health materials are easily accessible with an Internet connection, but the readability of its content may limit practical use by patients. Objective: The goal of our study was to assess the readability of the most commonly searched Internet health education materials for cardiovascular diseases accessed via Google. Methods: We selected 20 commonly searched cardiovascular disease terms: aneurysm, angina, athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
(37 reference statements)
5
20
0
6
Order By: Relevance
“…National organisations encourage the composition of Internet-based patient educational materials at the fifth-to sixth-grade level. 26 Numerous studies in the medical field have shown that Internet-based patient educational materials do not comply with national readability recommendations. [6][7][8]16,19 To our knowledge, this study is the first to evaluate readability in the field of paediatric cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…National organisations encourage the composition of Internet-based patient educational materials at the fifth-to sixth-grade level. 26 Numerous studies in the medical field have shown that Internet-based patient educational materials do not comply with national readability recommendations. [6][7][8]16,19 To our knowledge, this study is the first to evaluate readability in the field of paediatric cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous studies on a wide array of health conditions ranging from pancreatic cancer to carpal tunnel syndrome. 6,[13][14][15][16][17][18][19][20][21][22][23][24][25] In our study, 28 total websites were each evaluated by 9 readability tests, for a total of 252 individual evaluations. We found only 18 (7.14%) of the 252 individually graded websites were rated at an eighthgrade reading level, and none (0/252) were graded at a seventhgrade reading level or lower.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Examination of patient-directed health information from a wide variety of specialties has consistently found that the materials exceeded the reading-level recommendations of the NIH and AMA. 6,[13][14][15][16][17][18][19][20][21][22][23][24][25] In addition, health information must be understandable or presented in a way that makes sense to the patient and inform appropriate decisions regarding care.…”
Section: Introductionmentioning
confidence: 99%
“…A minority of CAD websites included in our study (13/54, 24%) received a GFI score of less than twelve, corresponding with a reading level at or below that of a high school senior. A recent study also found that 99.5% of online cardiovascular disease-related health education materials recommended by the AMA were written above the fifth to sixth-grade level [29]. Our study found that the CAD websites' readability was higher than recommended, which could have far-reaching implications for patients' health literacy [29].…”
Section: Renderxmentioning
confidence: 53%
“…A recent study also found that 99.5% of online cardiovascular disease-related health education materials recommended by the AMA were written above the fifth to sixth-grade level [29]. Our study found that the CAD websites' readability was higher than recommended, which could have far-reaching implications for patients' health literacy [29]. However, it is important to note that readability is only one element of literacy.…”
Section: Renderxmentioning
confidence: 54%